Probiotics administration as a prevention for postoperative infectious complications in colorectal cancer patients: A literature review - Angela Dalimarta; Wiji Lestari (World Nutrition Journal, 2021)
Background Colorectal cancer is the third leading cause of death from cancer in adults in the United States, with increasing prevalence in other countries. Radical resection is the gold standard of treatment in most cases of colorectal cancer, with a high rate of postoperative complications. Perioperative probiotics can improve the immune response and the postoperative intestinal microbiota environment. Although several studies have shown the benefits of probiotics in preventing postoperative complications of infection, the administration of perioperative probiotics in colorectal cancer patients is still controversial. Objective. The purpose of this critical appraisal is to know the effectiveness of administering probiotics to prevent infectious complications in colorectal cancer patients. Methods. Literature research using Pubmed, Cochrane, and EBSCOhost was carried out and 2 articles were obtained in the form of meta-analysis using STATA v11 and Revman v5.2 that was critically examined using the FAITH method. A comprehensive search for all studies was done to find all relevant studies using both MeSH terms and text words. The article should describe the assessment of quality and criteria used in method section, also provide information on the quality of individual studies in result section to minimize bias. The result section should state whether heterogeneity exists and mention possible reasons. Results. Based on 2 meta-analyses that have been critically examined, which each consisting of 13 and 7 studies, giving probiotics can reduce the overall infection rate after colorectal cancer surgery. One meta-analysis showed an odds ratio (OR) of 0.51 (95% CI: 0.38 – 0.68, p = 0.00). Probiotics, such as Lactobacillus acidophilus and Bifidobacterium longum can also reduce the incidence of surgical site infections (OR = 0.59, 95% CI 0.39 – 0.88, p = 0.01) and pneumonia (OR = 0.56, 95% CI 0.32 – 0.98, p = 0.04). Probiotics did not provide statistically significant benefits in preventing urinary tract infections, leakage of anastomosis, and duration of postoperative pyrexia compared to the control group. Seven articles analyzed in the second meta-analysis showed probiotics to be useful in preventing postoperative infections with OR 0.5388 (95% CI, 0.4058-0.7154, P <0.0001). Conclusions. Combination of more than one strain of probiotics such as Lactobacillus and Bifidobacterium is promising for the prevention of infections in patients undergoing colorectal cancer surgery.